2003
DOI: 10.1007/s00705-003-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mutations in the VP2/VP4 cleavage site of Swine vesicular disease virus on RNA encapsidation and viral infectivity

Abstract: We studied VP0 cleavage of Swine vesicular disease virus (SVDV), a member of the Picornaviridae using a full-length cDNA copy of the Dutch SVDV isolate. The influences of mutations, introduced at the cleavage site of SVDV, on VP0 cleavage, RNA encapsidation and viral infection were studied. Double mutations at asparagine (VP0 aa 69) and serine (VP0 aa 70) resulted in no cleavage of VP0 and 100% inhibition of virus production. Mutation of the asparagine into threonine or phenylalanine resulted in a low amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Earlier studies have reported about the significance of mutation in Cysteine having higher probability in causing disease (Vitkup et al, 2003). Besides, the asparagine into threonine mutation had been stated to trigger a decreased amount of cleaved VP0, one of the structural proteins of the Swine vesicular disease virus (SVDV),a nonenveloped single positive stranded RNA virus (Rebel et al, 2003). Thus, based on the results obtained, the present study reports for the first time the possible association of C1483W and N1530T mutations with high viral load in ALF and disease severity in pregnant women.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 58%
“…Earlier studies have reported about the significance of mutation in Cysteine having higher probability in causing disease (Vitkup et al, 2003). Besides, the asparagine into threonine mutation had been stated to trigger a decreased amount of cleaved VP0, one of the structural proteins of the Swine vesicular disease virus (SVDV),a nonenveloped single positive stranded RNA virus (Rebel et al, 2003). Thus, based on the results obtained, the present study reports for the first time the possible association of C1483W and N1530T mutations with high viral load in ALF and disease severity in pregnant women.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 58%
“…4, our VLP-ELISA using neutralizing antibody 3H10 did not detect SVDV-specific antibodies in the (5,24). Several epitopes involved in neutralization of SVDV have been identified on the capsid surface (5,23,25,29,34), and although immune response in pigs is induced by linear epitopes (24), conformational epitopes are known to be the most immunogenic (5). In preliminary work, neutralizing antibodies (VN titers of up to 1:1,000) were developed in BALB/c mice vaccinated with our VLPs in Freund's adjuvant, although high neutralizing antibody titers were elicited by inactivated SVDV antigen (VN titers Ͼ 1:3,200) in mice (data not shown).…”
Section: Discussionmentioning
confidence: 91%
“…These structural proteins can then self-assemble to form empty capsid particles, which are composed of 60 copies of each structural protein (4,36). The final step in virion assembly involves cleavage of structural protein VP0 into VP4 and VP2 during encapsidation of viral RNA (4,34,36).…”
mentioning
confidence: 99%
“…In contrast, the particles with a density of 1.285 g/cm 3 were empty particles (Figure d) that did not contain the virus genome. Empty virus particles are known to be produced as a natural product in most picornavirus‐infected cells, and these particles are usually generated without cleavage of the precursor (VP0) into VP2 and VP4 (Basavappa et al., ; Curry et al., ; Rebel, Leendertse, Dekker, & Moormann, ). In the present study, we found three protein bands—that is VP1, VP3 and an unknown protein band with a molecular mass of ~32 kDa—but bands corresponding to VP2 and VP4 were not found.…”
Section: Discussionmentioning
confidence: 99%